Índice de CHARLSON como predictor de mortalidad en pacientes con insuficiencia cardiaca del Hospital General Isidro Ayora de Loja - Carrillo Obando, Cristhian Michael (2021)
Heart failure is the leading cause of hospitalization in elderly people, and is also a general and hospital mortality problem. In order to identify comorbidities in patients with a diagnosis of heart failure and its correlation with mortality and predictive validity of the Charlson Index for this event, a descriptive, retrospective study was carried out in 117 patients discharged from Hospital Isidro Ayora in the period between March 2014 - June 2018, who were selected by inclusion and exclusion criteria. Absolute and relative frequencies, X2 tests and the ROC curve were calculated. All statistical tests were computed with a significance level of 5%. The study found a predominance of men (53.0%), married (52.1%), and aged ≥80 years (49.6%), of urban origin (60.7%) and primary education (40.2 %). Hospital stay was generally short (≤7 days) in 41%. The main comorbidity was hypertension, present in 36.7% and the majority (63.2%) had two comorbidities. Likewise, a relationship was found between the low level of education and the number of comorbidities (p = 0.05). The high comorbidity was associated with greater death one year after discharge (p = 0.000). The ROC curve of 0.844 validates the Charlson index as a predictor of mortality in patients with heart failure admitted in Isidro Ayora Hospital. It is concluded that the increase in comorbidities increases mortality one year after discharge, while the Charlson Index turned out to be an excellent predictor of this event at the same time of discharge. Keywords: older adults, predictive value, chronic diseases, survival.